2012
DOI: 10.1074/jbc.m111.282210
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C (PKC)ζ-mediated Gαq Stimulation of ERK5 Protein Pathway in Cardiomyocytes and Cardiac Fibroblasts

Abstract: Background: We have recently described that G␣ q acts as an adaptor protein that facilitates PKC-mediated activation of ERK5. Results: Our results show that PKC is essential for Gq-dependent ERK5 activation in cardiomyocytes and cardiac fibroblasts. Conclusion: This novel signaling axis plays a key role in cardiac hypertrophy programs. Significance: The G␣ q /PKC/ERK5 pathway would be active in such pathological settings, providing new therapeutic targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 76 publications
1
19
0
1
Order By: Relevance
“…As discussed earlier, ERK5 is highly specific, and its overexpression in cultured cells does not activate other MAPKs (English et al, 1995). Many studies demonstrated that MEK5-ERK5 signaling is activated by growth stimuli via RTKs and GPCRs (Kato et al, 1997, Kamakura et al, 1999, Garcia-Hoz et al, 2012), as well as by oxidative and osmotic stresses (Abe et al, 1996). Epidermal growth factor receptors have been shown to mediate hypertrophic signaling through an MEK5-ERK5-MEF2A pathway in H9c2 cardiomyocytes (Lee et al, 2011).…”
Section: Mapks In Chronic Cardiac Stress (Hypertrophy and Heart Famentioning
confidence: 99%
“…As discussed earlier, ERK5 is highly specific, and its overexpression in cultured cells does not activate other MAPKs (English et al, 1995). Many studies demonstrated that MEK5-ERK5 signaling is activated by growth stimuli via RTKs and GPCRs (Kato et al, 1997, Kamakura et al, 1999, Garcia-Hoz et al, 2012), as well as by oxidative and osmotic stresses (Abe et al, 1996). Epidermal growth factor receptors have been shown to mediate hypertrophic signaling through an MEK5-ERK5-MEF2A pathway in H9c2 cardiomyocytes (Lee et al, 2011).…”
Section: Mapks In Chronic Cardiac Stress (Hypertrophy and Heart Famentioning
confidence: 99%
“…The selective inhibitor of PKC (MPI-PKC) strongly decreased the A 1 AR-induced plasmalemmal Ca 2ϩ influx in atrial cells (Ϫ86%) whereas this inhibitor had a slighter effect (p Ͻ 0.01) in ventricular cells (Ϫ56%), supporting a predominant role for PKC in adenosinergic signaling in atrial cells. Adenosine A 2A receptor activation has been shown to induce translocation/activation of PKC (60,61), and the G q protein can be regarded as a scaffold protein capable of recruiting PKC into a complex that activates the ERK pathway in neonatal and adult cardiomyocytes and fibroblasts (62). We also recently found that A 1 AR activation induces pacemaking and conduction disturbances through downstream activation of ERK pathway in the developing heart (11).…”
Section: Journal Of Biological Chemistry 26695mentioning
confidence: 99%
“…Yine G q molekülü MEK5 aracılığında ERK5 yolağı-nın aktivasyonunu düzenler [105]. Epitel hücrelerinde GPCR reseptörleri ile PKCζ ilişkili ERK5 yolağının etkinleşmesinde G q nün adaptör protein olarak rol oynadı-ğı [106], kardiyak miyozit ve fibroblast hücrelerinde de PKCζ 'nın G q bağımlı ERK 5 yolağının aktifleşmesinde gerekli olduğu bildirilmektedir [107],.…”
Section: Mapk' Ların G Q İle Düzenlenmesiunclassified